Beyond ‘Good’ and ‘Evil’: Breaking Down Binary Oppositions in Holocaust Representations of ‘Privileged’ Jews - Brown, Adam (History compass, 2010)
In 1986, Auschwitz survivor Primo Levi’s paradigmatic essay entitled ‘The Grey Zone’ highlighted the complex and sensitive issue of so-called ‘privileged’ Jews, an issue that remains at the margins of popular and academic discourse on the Holocaust. ‘Privileged’ Jews include those prisoners in the Nazi concentration camps and ghettos who held positions that gave them access to material and other benefits whilst compelling them to act in ways that have been judged both self-serving and harmful to fellow inmates. The unprecedented ethical dilemmas that confronted ‘privileged’ Jews may be viewed as exemplifying the ‘limit’ events or experiences that were characteristic of the Holocaust, situating them at the threshold of representation, understanding and judgement. Levi’s essay singles out history and film as particularly predisposed to a simplifying trend he identifies - the ‘Manichean tendency which shuns half-tints and complexities,’ and resorts to the black-and-white binary opposition(s) of ‘friend’ and ‘enemy,’‘good’ and ‘evil.’ In the case of ‘privileged’ Jews in particular, such binary oppositions would appear to be inadequate. Adopting an interdisciplinary approach that incorporates the fields of history, philosophy and literature, this paper analyses representations of ‘privileged’ Jews, particularly those prisoners of the Sonderkommandos who were forced to work in the crematoria. The paper demonstrates how easily the boundary Levi maps out for moral judgement can be crossed. It is shown that while Levi suggests judgement should be suspended when confronted with the experiences of victims in extremis, moral evaluations of ‘privileged’ Jews permeate discussions and representations of the Holocaust. When confronted with such emotionally and morally freighted issues, judgement may itself be seen as a ‘limit of representation.’